Model of Improving Employee Performance through Organizational Commitment to Pulp Industry in Sumatera - Junaidi, Junaidi; Situngkir, Sihol; Edward, Edward; Adriani, Zulfina (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study aims to describe and analyze Model of improving employee through organizational commitment to Pulp Industry in Sumatera. The research method used descriptive quantitative. The sample of this study used probability sampling technique. The sample selection criteria was employees of the pulp industry in Jambi, Pekanbaru and Palembang. Beverage Development with a total of 240 samples obtained from Sumatera (Jambi, Pekanbaru and Palembang). Data analysis was performed by using descriptive statistical analysis and inferential statistical analysis. The data obtained was processed using a component-based or variance-based Structural Equation Modeling (SEM) analysis which is known as Partial Least Square (PLS). It was found that the direct influence of competence, career development and extrinsic motivation and organizational commitment had a positive and significant effect on employee performance in pulp industry, then the indirect effect of competence, career development and extrinsic motivation had a positive and significant effect on employee performance mediated by organizational commitment.